Pentingnya pengetahuan nutrisi untuk meningkatkan performa atlet pencak silat - Dinda Oktaviani Puspitaningrum; Isna Hikmawati; Supriyadi Supriyadi; Meida Laely Ramdani (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Pencak silat is a traditional martial art from Indonesia that requires sufficient energy to avoid nutritional problems. Malnutrition can reduce endurance, which can be caused by a lack of knowledge about nutrition.Objective: Knowing the relationship between nutritional knowledge and nutritional status in martial arts athletes.Methods: Cross sectional design, the sample was 66 martial arts athletes with total sampling technique. The research was conducted at SMA Negeri 1 Bawang, Tapak Suci Wanadadi hermitage and SMP Negeri 3 Banjarnegara, in May -September 2024. The research instrument used a questionnaire to assess nutritional knowledge by providing 30 questions and assessing nutritional status using the Body Mass Index (BMI). Statistical analysis using Chi-square test at α ≤ 0,05.Results: Nutrition knowledge in the domain of nutrient composition was partial at 53,0%, knowledge in the domain of nutrient-rich foods was also lacking at 51,5%. However, knowledge in the domain of the impact of nutritional deficiencies on athletes was good at 80,3%. Nutritional status is mostly normal 63,6%. There is no relationship between nutritional knowledge and nutritional status in martial arts athletes (p = 0,205).Conclusion: There is still low knowledge of athlete nutrition in the domain of nutrient composition and nutrient-rich foods that can have an impact on the nutritional status of athletes.